Rethinking The moral problem - Smith Michael (Belgrade Philosophical Annual)
Are intrinsic desires subject to reasoned criticism, and if they are, what is about them that makes them subject to such criticism? It is argued that though the answer given to this question in The Moral Problem is wrong, a more promising answer can be found if we attend to the metaphysics of agency.